On the importance of Sumatra’s East Coast for waterbirds, with notes on the Asian Dowitcher Limnodromus semipa1matus - Marcel J Silvius (KUKILA, 1988)
Since 1984, three surveys were conducted along the east coast of Sumatra. Several coastal wetlands appeared to be of international importance for waterbirds (according to the criteria of the Ramsar Convention). More than 10,000 large waterbirds were identified, including large numbers of Milky Storks Mycteria cinerea and Lesser Adjutants Leptoptilos javanicus,, and over 100,000 migratory waders (28 species) were counted. The observation of a minimum total of 3,800 Asian Dowitchers Limnodromus semipalmatus indicates that the east coast of Sumatra is the main wintering area of the species. In areas of high conservation importance, data were collected on habitat and threats. Several of these areas face heavy reclamation pressure, which necessitates urgent conservation action.